(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25^2 -1)(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25-(a.b^2-a) với a= -1 , b=(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25 25(a^2 +b^2 -1)-(a.b^2(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25-a) với a= -1 (a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25=5 25
A=2+2²+2³+2⁴+...±2²⁰⁰
2A = 2(2+2²+2³+2⁴+...±2²⁰⁰)
2A = 2²+2³+2⁴+...±2²⁰⁰+ 2^201
2A - A = (2²+2³+2⁴+...±2²⁰⁰+2^201) - ( 2+2²+2³+2⁴+...±2²⁰⁰ )
A = 2^201-2
Chúc bạn hok tốt